Transformasi Sosial melalui Digitalisasi Usaha: Pelatihan E-Commerce Bagi Pelaku Usaha Keripik Keladi Kartika - Melda Agnes Manuhutu; Natasya Virginia Leuwol; Agustina Agustina; Elisabeth Elisabeth; Boyke Boyke; Ferdynand Ferdynand; Sakarias Sakarias; Lulu Jola Uktolseja (Lembaga Pengembangan Kinerja Dosen, 2025)
The social transformation that has occurred in the digital era has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adapt to developments in information technology to increase competitiveness and expand market reach. One form of this adaptation is the use of e-commerce platforms as a means of marketing and managing their businesses online. This community service activity aims to empower the Kartika Taro Chips MSME through the introduction and implementation of an e-commerce platform based on Odoo.com, an integrated Enterprise Resource Planning (ERP) system. This activity was carried out by students of the Information Systems Study Program, Faculty of Computer Science, Victory University Sorong, with the assistance of lecturers from the Information Systems and Sociology fields. The training method includes several stages, namely: the stage of material preparation and analysis of participant needs, the implementation of a workshop that includes the installation and configuration of Odoo.com, and the post-training mentoring stage to ensure the sustainability and independence of participants in managing their online stores. The results of the training showed that participants were not only able to build and manage online stores independently, but also understood the basic concepts of ERP systems and experienced a significant increase in digital literacy. From a sociological perspective, this activity reflects a technology-driven social transformation process, where MSMEs are actively expanding their social networks through digital spaces and increasing their involvement in the digital economy. This demonstrates that integrating technological and social approaches can be a relevant MSME empowerment model in local contexts. Overall, this training has had a positive impact on strengthening MSMEs' digital capacity and opening up new opportunities for sustainable business development in the era of digital transformation.